Comparing quality of life, stress perception and quality of social networks in a community-based brain injury program - Prudhomme , Barbara (International Journal of Psychosocial Rehabilitation, 2016)
Objective: To study perceptions of quality of life, stress, and social networks/social connectedness in persons living with acquired brain injury. Design: This was a two-group comparative survey study, analyzing results from a common questionnaire. Participants: 83 adults with chronic brain injury, between the ages of 23-80, living within the community, were placed in one of two groups depending on whether they attended Krempels Center, a community-based center offering day programming for chronic brain injury. Main Outcome Measures: An outcomes questionnaire was compiled from other assessments used in the field, in order to identify individual perception on several psychosocial variables. Results: Several significant differences were found between groups, suggesting that Krempels Center members of at least 6 months duration were less stressed overall, had stronger perceptions of social connectedness, and had higher quality of life perception than did the community sample participants. Conclusion: Individuals with acquired brain injury are faced with daily challenges related to quality of life, management of stress, and social connectedness and opportunities to engage in the community around them. Applying a group-based approach and individualized/family support, offers an effective best-practice model for community based services post-rehabilitation.